The main currents (schools) of thought about the informal economy - Cristian MARINESCU; Ileana VALIMĂREANU (MIRCIOI) (Revista de Management Comparat International)
Starting from the various interpretations of the concept of "informality", which can be associated with both negative aspects (underground economy, tax evasion, undeclared work, lack of productivity, lack of social protection, unfair competition) and positive aspects (a source for the poor, who have no alternative), this paper aims to review the main conceptual debates over the term "informality", opinions that can be synthesized in four currents or schools of thought, respectively: The dualist school, Structuralist School, Legalistic School and Voluntaristic School